Interaksi Hadis dan Budaya: Interpretasi Ali Mustafa Yaqub dalam Kitab Al-Turuq Al-Sahihah Fi Fahm Al-Sunnah Al-Nabawiyah - Khalilurrahman, As'ad; Ichwayudi, Budi; Shobri, Alwi; Akbar, Riko (Jurnal Diskursus Islam, 2024)
The source of religious teachings is the Qur'an and hadith (sayings and actions of Prophet Muhammad). The birth of both is closely related to the culture and customs of the society at that time. The Prophet used culture as a medium to convey his message. The actions of the Prophet served as an example for humanity, especially Muslims, in the world. These behaviors and traits are referred to as the "sunnah." One example of the Prophet's habits is wearing the imamah or turban, letting his hair grow long, and many other aspects related to the Prophet's life. As devout followers, it is important to practice everything the Prophet did as a form of reverence for him. However, the challenge arises because every place has different cultures and customs. This becomes an issue when the Prophet's habits, as depicted in the hadiths, are not followed due to reasons not related to religious matters. Consequently, practices that are not considered acts of worship (ibadah) may be abandoned according to the local culture and traditions. Abstrak Sumber ajaran agama adalah al-Qur’an dan hadis. Lahirnya keduanya tidak lepas dari budaya dan kebiasaan masyarakat pada masa itu. Nabi menggunakan budaya sebagai media dalam menyampaikan risalahnya. Tindakan yang dilakukan Nabi adalah suri tauladan atau contoh untuk umat manusia khususnya muslim didunia. Prilaku dan sifat itulah disebut dengan sunnah. Salah satu contoh kebiasaan Nabi adalah menggunakan imamah atau sorban, membiarkan rambutnya panjang dan banyak lagi hal-hal yang berkenaan dengan kehidupan Nabi. Sebagai umat yang taat beragama perlulah utuk mengamalkan semua yang dilakukan Nab dalam bentuk rasa cita kepada Nabi. namun masalahnya adalah setiap tempat mempunyai budaya dan istiadat yang berbeda-beda. Hal ini menjadi masalah ketika kebiasaan Nabi yang tergambar dalam kitab-kitab hadis tidak diamalkan dengan alasan bukan perkara agama. Sehingga amalan yang ranahnya bukan ibdah boleh ditinggal sesuai budaya, tradisi masyarakat setempat.